Journals as a Feminist Playground - Case, Mary Anne (Columbia Journal of Gender and Law, 2003)
When I told the organizers of this symposium I wished to take as my topic the problems of disagreement among feminists, they put me on a panel they had titled “Why Do We Eat Our Young?: Journals As a Feminist Battleground.” Like Katherine Franke, whose paper also proceeds from the premise that “we disagree badly as feminists,”‘ I, too, will resist the title given our panel by changing one word in it and explaining why the given title will not do. In speaking of journals as a feminist playground rather than battleground, I shall say something about the relationship I perceive between playgrounds and battlegrounds, play and battle. I will also take issue with the first half of our panel’s assigned title by arguing that the question to pose is not why (or even whether) we eat our young but how we honor our mothers. My thoughts are prompted by comments given to me early in my career when I circulated an article of mine on feminist jurisprudence to a senior feminist theorist at a prestigious law school. Although generally encouraging, she was quite troubled by one passage. In that passage, after noting that “I myself think it is important to remember that feminism is not simply about women” and urging a “focus on how men as well as women fit into the world,” I had dropped a footnote saying, “Not all feminist legal theorists would agree with me.” As an example, I had cited Christine Littleton’s “making a claim” Littleton herself had described as one she had “only recently begun to understand as controversial: feminism is about women….. The claim is merely that, even though many feminists do sincerely care about men, caring about men is not what feminism is about.” According to my reader, my mere admission of a clear disagreement among feminist theorists risked undermining the discipline as a whole. You cannot say that, she told me. You cannot say, “Some feminists think x and I think the opposite.” That is just what unsympathetic male critics are waiting for, she warned. They will reward you for saying such things, but they will use what you say to hurt other women.